Long Non-Coding RNA AL513318.2 as ceRNA Binding to hsa-miR-26a-5p Upregulates SLC6A8 Expression and Predicts Poor Prognosis in Non-Small Lung Cancer - Fan, Yongfei; Zhou, Yong; Li, Xinwei; Lou, Ming; Gao, Zhaojia; Yuan, Kai; Tong, Jichun (Frontiers in Oncology, 2022)
Background Studies have demonstrated that the regulatory role of competitive endogenous RNA (ceRNA) networks is closely related to tumorigenesis, which provides new targets for tumor therapy. In this study, the focus was to explore the ceRNA networks that regulate SLC6A8 expression and their prognosis in non-small cell lung cancer (NSCLC). Methods Firstly, the Cancer Genome Atlas (TCGA) data combined with immunohistochemical staining was used to compare SLC6A8 expression in NSCLC tissues and normal tissues. Thereafter, samples from the immunohistochemical staining of NSCLC were integrated with clinical follow-up data for prognostic analysis. The Starbase database was employed to search for SLC6A8-targeted miRNAs and lncRNAs, and survival analysis was performed using clinical data from TCGA to obtain SLC6A8 expression and prognosis-related ceRNA networks. Finally, the prognostic and therapeutic prospects of SLC6A8 in NSCLC were further analyzed from methylation sites and the immune microenvironment. Results The study results revealed that SLC6A8 was significantly overexpressed in NSCLC tissues compared to normal tissues, and clinical follow-up data showed that the overexpression group was associated with poor prognosis. In addition, the Starbase data combined with TCGA clinical data analysis demonstrated that the AL513318.2/hsa-miR-26a-5p/SLC6A8 network regulates SLC6A8 overexpression in NSCLC and is associated with poor prognosis. Methylation analysis revealed that 11 methylation sites were closely associated with the prognosis of NSCLC. In addition, the immune prognostic risk model showed that the high-risk group was associated with a poorer prognosis than the low-risk group, despite showing a better immunotherapy outcome. Conclusion In summary, the AL513318.2/hsa-miR-26a-5p/SLC6A8 network upregulates SLC6A8 expression in NSCLC and is associated with poor prognosis. Therefore it may be a prognostic biomarker of NSCLC and a potential therapeutic target.